The scale of occupational stress: the Bristol stress and health at work study - Smith, Andrew; Sarbjit, Johal; Wadsworth, Emma; Davey Smith, George; Peters, Tim (Sudbury, 2000)
"The research reported in this report has three main aims. First, to determine the scale and severity of occupational stress in a random population sample. Second to distinguish the effects of stress at work from those of general life stress. Finally, to determine whether objective indicators of health status and performance efficiency were related to perceived occupational stress ..."